(untitled) (Homoeopathy for All, 2022)
Rheumatoid arthritis (RA) is a chronic disease in which various joints in the body are inflamed, leading to swelling, pain, stiffness, and the possible loss of function. The word arthritis means inflammation of the joint (“arthr” meaning joint and “itis” meaning inflammation). Inflammation is a medical term describing pain, stiffness, redness and swelling. Homoeopathy is a remarkable resource for those dealing with joint disorders. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of this disorder.